Hervormde Barthiaanse Skrifbeskouing: Waarheidsbegrip - Malan, Gert J. (HTS teologiese studies, 2017)
The ‘ Hervormde ’ blend of Barthian view of Scripture leads to a specifically nuanced concept of biblical truth. Biblical truth is neither knowledge, dogma or faith propositions, nor historical, scientific or geographical truth. Biblical truth is a Person, sharing in dialogue with humanity regarding a relationship of God for humanity. Biblical truth is relational and metaphorical. Its imperatives are demythologisation, and ideological and cultural critique. This concept of truth is in contrast to the truth concept of most church members, because of their literal and often fundamentalist views of Scripture. In order to convey understanding of the truth concept, the ‘ Hervormde ’ view of Scripture should be discussed with them. A confession should be formulated for post-modern believers.